Enhanced Antiwear Property of Cu-Sn-Bi Bimetal Composites with TiB2 under Different Working Conditions. Issue 1 (22nd December 2021) - Yang, Dongya; Li, Zhenyu; Zhao, Gengrui; Wang, Honggang; Ren, Junfang; Gao, Gui; Liu, Wenguang
Abstract: The present study investigated the effect of TiB2 on the tribological properties of CuSn10Bi3 bimetallic bearing materials. CuSn10Bi3 samples with different contents of TiB2 were fabricated by powder sintering technology. Their metallographic structures and tribological characteristics under different working conditions were analyzed and compared. The results showed that TiB2 refined the copper alloy grains, passivated the grain boundary edges, and reduced the surface porosity of the sample. When the content of TiB2 was 1%, the wear rate under different oil conditions (oil-rich, oilless, and dry friction) was reduced by 42–95%. The sharp decrease in the wear rate was attributed to the enhancement of the micrograin structure of the copper alloy matrix material by TiB2 hard particles with antiwear properties and the high hardness and high wear resistance of TiB2 . The wear tracks were analyzed using scanning electron microscopy and energy-dispersive spectroscopy, and it was concluded that the addition of TiB2 enhanced the wear resistance.